Do Corporate Governance and Bank-Specific Factors Matter On Banking Financial Performance? - Lilik Handajani; Akram Akram; Ayudia Sokarina (Universitas Muhammadiyah Malang, 2024)
Purpose: This study explores and presents empirical evidence on the influence of self-assessment of bank corporate governance and bank-specific factors on the financial performance of commercial banks in Indonesia. Methodology/approach: We conducted the study on 35 Indonesian public banks listed on the Indonesia Stock Exchange from 2017 to 2021. Using structural equation modeling, a thorough analysis was performed on a dataset of 160 observation samples that were carefully selected through purposive sampling. Findings: This study found that the implementation of corporate governance, which is proxied by the rating of self-assessment of corporate governance, and bank-specific factors significantly affect bank financial performance. The better the corporate governance self-assessment rating, the better the bank's financial performance. Other results indicate that bank-specific factors, as reflected by bank ownership, size, and diversification, significantly positively contribute to bank financial performance. Practical implications: This research aims to provide valuable insights that can support the Indonesian Financial Services Authority (OJK) in implementing effective corporate governance practices. It focuses on enhancing risk management, strengthening the bank's internal capacity, and ensuring compliance with regulations to promote best practices in bank management. Originality/value: This study provides new insight by examining the factors influencing financial performance in the banking sector, focusing on bank-specific factors and the regulatory aspects of Indonesian banking governance.